Agricultural crop exposure and risk of childhood cancer: new findings from a case–control study in Spain. Issue 1 (December 2016) - Gómez-Barroso, Diana; García-Pérez, Javier; López-Abente, Gonzalo; Tamayo-Uria, Ibon; Morales-Piga, Antonio; Pardo Romaguera, Elena; Ramis, Rebeca
Abstract Background Childhood cancer is the main cause of disease-related death in children in Spain. Although little is known about the etiology, environmental factors are potential explanations for a fraction of the cases. Previous studies have shown pesticides to be associated with childhood cancer. The difficulty of collecting personal environmental exposure data is an important limitation; this lack of information about pesticides motivates the development of new methods to subrogate this exposure. We developed a crop exposure index based on geographic information to study the relationship between exposure to different types of crops and risk of childhood tumors. Methods We conducted a population-based case–control study of childhood cancer covering 3350 cases and 20, 365 controls in two Spanish regions. We used CORINE Land Cover to obtain data about agricultural land use. We created a 1 km buffer around every child and calculated the percentage of crop surface within the buffer (Global Crop Index) for total crops and for individual types of crops. We fitted mixed multiple unconditional logistic regression models by diagnostic group. Results We found excess of risk among children living in the proximity of crops. For total crops our results showed excesses of risk for almost all diagnostic groups and increasing risk with increasing crop index value. Analyses by region and individual type of crop also showed excess of risk. Conclusion The results suggest that living in the proximity of cultivated land could be a risk factor for several types of cancer in children.